Rotavirus antigen detection in serum samples from children with acute gastroenteritis in Belém, Pará State, Brazil - Justino, Maria Cleonice Aguiar (2020)
or thousands of deaths due to diarrhea worldwide, especially in developing countries. Recent studies have indicated the presence of RV antigens in the serum (antigenemia) and feces of animals and humans, which may be related to extraintestinal clinical manifestations and increased disease severity. This study was conducted in a children's clinic located in Belém, Pará State, Brazil, and aimed to detect antigenemia caused by RV in children hospitalized for AGE. The study population was composed of 566 children, from whom 452 paired fecal and serum samples were collected for RV antigen detection using immunoassays (ELISA). Positive results were found in 24% (109/452) of fecal samples; antigenemia was detected in 37.5% (41/109) of children. Disease severity was analyzed using Ruuska and Vesikari's scoring system and no statistically significant difference was observed between patients with or without antigenemia (p = 0.120); however, a greater number of vomiting episodes and longer duration of vomiting were observed in patients with antigenemia than those without antigenemia (p = 0.015 and p = 0.002, respectively). Antigenemia is frequently identified in children hospitalized for AGE caused by RV, and is associated with a greater number of vomiting episodes and longer duration of vomiting in Belém, Brazil. The results enabled a better understanding of the pathogenesis of RV infections, especially in vaccinated children. However, a comprehensive analysis is necessary, including molecular tests for the genotypes involved for completing the achieved results.